Antimicrobial and Cytotoxic Naphthoquinones from Microbial Origin: An Updated Review - Kashi, Marziyeh E.; Ghorbani, Mahdiyeh; Badibostan, Hasan; Seidel, Veronique; Hosseini, Seyed Hamzeh; Asili, Javad; Shakeri, Abolfazl; Sahebkar, Amirhossein (Mini Reviews in Medicinal Chemistry, 2024)
Naphthoquinones (NQs) are small molecules bearing two carbonyl groups. They have been the subject of much research due to their significant biological activities such as antiproliferative, antimicrobial, anti-inflammatory, antioxidant, and antimalarial effects. NQs are produced mainly by bacteria, fungi and higher plants. Among them, microorganisms are a treasure of NQs with diverse skeletons and pharmacological properties. The purpose of the present study is to provide a comprehensive update on the structural diversity and biological activities of 91 microbial naphthoquinones isolated from 2015 to 2022, with a special focus on antimicrobial and cytotoxic activities. During this period, potent cytotoxic NQs such as naphthablin B (46) and hygrocin C (30) against HeLa (IC50=0.23 μg/ml) and MDA-MB-431 (IC50=0.5 μg/ml) cell lines was reported, respectively. In addition, rubromycin CA1 (39), exhibited strong antibacterial activity against Staphylococcus aureus (MIC of 0.2 μg/ml). As importance bioactive compounds, NQs may open new horizon for treatment of cancer and drug resistant bacteria. As such, it is hoped that this review article may stimulates further research into the isolation of further NQs from microbial, and other sources as well as the screening of such compounds for biological activity and beneficial uses.
Keywords: bioactive compounds